MODEL KEPEMIMPINAN MENURUT PLATO DAN RELEVANSINYA TERHADAP PEMIMPIN MASA KINI - Berlina Berlina; Elsani Bungan Layuk, Liliana Yanti Randa, Ratna Dekak, Suleman Borotoding (ADISAM PUBLISHER, 2025)
This paper shows and discusses the concept of leadership according to Plato and how it is relevant in today’s leadership. Leaders are very much needed in an organization/company, institution or country. Learning from the concept of leadership according to Plato, which assumes that the ideal state is a state led by a philosopher are people who love truth and wisdom, a country can achieve the goals thet have been set previously. Seeing the leaders of tody’s era, especially in Indonesia, there are many great leaders, smart, but do not love the truth. Many leaders are still doing corruption, doing money pilitcs, and so on. Therefore, Plato assumes that an ideal state is a state led by a philosopher who loves truth and wisdom. In compiling this paper, the author uses a descriptive qualitative research method, which uses souces from books, journals and other sources as a reference in compiling this paper